2017
DOI: 10.1007/s11205-017-1617-1
|View full text |Cite
|
Sign up to set email alerts
|

Social Capital Associated with Quality of Life Mediated by Employment Experiences: Evidence from a Random Sample of Rural-to-Urban Migrants in China

Abstract: Working-age migrants need to possess adequate social capital in order to secure a stable and satisfactory job so that they can pursue a better quality of life (QOL). The positive relationship between social capital and vocational experiences, including successful employment, has been well established. In this study we focused on testing a multi-step mediation model linking social capital with employment experiences, and further to QOL. Survey data from rural-to-urban migrants randomly selected from Wuhan, Chin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 83 publications
(141 reference statements)
2
17
0
Order By: Relevance
“…The utilization of essential public health services (EPHS) among old-aged migrants is another challenging issue [5,6], and migration status in the household registration system is the core factor hindering the utilization of public services [7,8]. Meanwhile, as the previous study reported that weak health literacy and economic status contributes to insufficient understanding or utilization of health insurance and EPHS [9].…”
mentioning
confidence: 99%
“…The utilization of essential public health services (EPHS) among old-aged migrants is another challenging issue [5,6], and migration status in the household registration system is the core factor hindering the utilization of public services [7,8]. Meanwhile, as the previous study reported that weak health literacy and economic status contributes to insufficient understanding or utilization of health insurance and EPHS [9].…”
mentioning
confidence: 99%
“…Further, Ommen et al [40] found that social capital, in the form of perceived trust, common values, and reciprocity in a workplace, had a significant positive association with job satisfaction after accounting for workload and professional experience. Chen et al [41] confirmed that social capital is positively associated with job satisfaction-both bonding and bridging capital.…”
Section: Social Capital and Job Satisfactionmentioning
confidence: 97%
“…Along with rapid and unevenly paced globalization, economic growth, and technological development, more and more medical and health issues with global impact emerge. Typical examples include growing health disparities, migration-related medical and health issues, issues related to internet abuse, the spread of sedentary lifestyles and lack of physical activity, obesity, increasing rates of substance abuse, depression, suicide and many other emerging mental health issues, and so on [10,23,36,42,[57][58][59][60]. GHRP is expecting to receive and publish more studies targeting these issues guided by a global health perspective and supports more researchers to look for global solutions to these issues.…”
Section: The Concept Of Global Impactmentioning
confidence: 99%
“…However, it would not be considered as global if the purpose is purely to pursue profit. A research study on a medical or health problem among rural-to-urban migrants in China [57,58,60] can be considered as global if the researchers frame the study with a global perspective and include an objective to inform other countries in the world to deal with the same or similar issues.…”
Section: Types Of Global Health Researchesmentioning
confidence: 99%